2017
DOI: 10.1080/14656566.2017.1288721
|View full text |Cite
|
Sign up to set email alerts
|

Triptans and migraine: advances in use, administration, formulation, and development

Abstract: Recent triptan development has focused on new administration methods and formulations, triptan combination therapies, treatment in menstrually related migraines, and novel serotonin receptor subtype agonists (5HTf). Areas covered: Clinical triptan research related to migraine was reviewed, analyzing EMBASE and PUBMED data bases from 01/01/2011 to 06/29/2016, with a focus on clinical trials of class 1 or 2 level of evidence. There have been advances in drug combination therapies, as well as administration devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 102 publications
0
19
0
2
Order By: Relevance
“…Triptans are 5-HT 1B/1D/1F agonists (7) inhibiting trigeminal calcitonin gene-related peptide (CGRP) release by hyperpolarizing nerve endings (8) and causing cranial vasoconstriction (9,10). Although beneficial in many patients, lack of effect and a relatively high incidence of side effects cause limitations (1113). A meta-analysis of 53 high-quality, placebo-controlled randomized clinical trials showed an average sumatriptan (100 mg per oral) response rate of 59% (95% CI 57–61) for any headache response, 29% (95% CI 27–31) for pain freedom and 20% (95% CI 18–21) for sustained pain freedom (14), showing that sumatriptan often results in pain reduction and not pain freedom.…”
Section: Introductionmentioning
confidence: 99%
“…Triptans are 5-HT 1B/1D/1F agonists (7) inhibiting trigeminal calcitonin gene-related peptide (CGRP) release by hyperpolarizing nerve endings (8) and causing cranial vasoconstriction (9,10). Although beneficial in many patients, lack of effect and a relatively high incidence of side effects cause limitations (1113). A meta-analysis of 53 high-quality, placebo-controlled randomized clinical trials showed an average sumatriptan (100 mg per oral) response rate of 59% (95% CI 57–61) for any headache response, 29% (95% CI 27–31) for pain freedom and 20% (95% CI 18–21) for sustained pain freedom (14), showing that sumatriptan often results in pain reduction and not pain freedom.…”
Section: Introductionmentioning
confidence: 99%
“…Triptans were introduced as a migraine treatment in the 1990s, implicating a major step forward in the better treatment for this disorder [ 17 ]. Since then, new research has focused on new administration methods and formulations, including triptan combination therapies with NSAIDs [ 18 , 19 ].…”
Section: -Ht 1 Receptors and Migrainementioning
confidence: 99%
“…Triptánok: A migrén kezelésében 1973-ban egy új szakasz kezdődött, amikor megpróbáltak az ergot származékoknál szelektívebb szerotonin agonistát szintetizálni, figyelembe véve a szerotonin jelenlétét a migrénes rohamok esetén [18][19][20].…”
Section: Orvostudományi éRtesítőunclassified